Expression and subcellular localization of the bromodomain-containing protein 7 is a prognostic biomarker in breast cancer. Issue 4 (April 2020) - Vivenza, Daniela; Garrone, Ornella; Brizio, Rodolfo; Mantovani, Fiamma; Del Sal, Giannino; Merlano, Marco; Crook, Tim; Lo Nigro, Cristiana
Abstract : Bromodomain-containing protein 7 (BRD7) is a member of the bromodomain-containing protein family. Previous studies suggest that BRD7 is predominantly localized in the nucleus, wherein it functions as a transcriptional regulator. Several lines of evidence imply a tumour suppressor function for BRD7. However, the importance of BRD7 in the pathogenesis of breast cancer is not well understood. We have investigated the expression, CpG island methylation and subcellular localization of BRD7 in breast cancer cell lines and clinical cases and thereby assessed its prognostic significance by correlating with clinical-pathological features and time-dependent clinical outcomes. We show that nuclear exclusion of BRD7 occurs commonly in breast cancer and is strongly associated with cases expressing wild-type p53. Moreover, clinical outcomes are significantly less favourable in cases with nuclear exclusion or loss of expression than those in which there is nuclear expression of BRD7. Methylation of the CpG island of BRD7 increases in breast cancer relative to normal breast tissue, but there is not an obvious correlation between methylation and reduced expression or between methylation and clinical outcomes. Overall, our results suggest that nuclear exclusion, rather than transcriptional silencing, is a common mechanism by which the tumour suppressor function of wild-type p53 is inhibited in breast cancer, and show that BRD7 is a promising candidate biomarker in breast cancer. Abstract : Supplemental Digital Content is available in the text.